VISTA/CTLA4/PD1 coexpression on tumor cells confers a favorable immune microenvironment and better prognosis in high-grade serous ovarian carcinoma - Jlassi, Aida; Rejaibi, Rim; Manai, Maroua; Sahraoui, Ghada; Guerfali, Fatma Zahra; Charfi, Lamia; Mezlini, Amel; Manai, Mohamed; Mrad, Karima; Doghri, Raoudha (Frontiers in Oncology, 2024)
Introduction Immunotherapy by blocking immune checkpoints programmed death/ligand (PD1/PDL1) and cytotoxic T-lymphocyte-associated protein 4(CTLA4) has emerged as new therapeutic targets in cancer. However, their efficacy has been limited due to resistance. A new- checkpoint V-domain Ig-containing suppressor of T cell activation (VISTA) has appeared, but the use of its inhibition effect in combination with antibodies targeting PDL1/PD1and CTLA4 has not been reported in ovarian cancer. Methods In this study, we investigated the expressions of VISTA, CTLA4, and PDL1 using immunohistochemistry (IHC)on 135 Formalin-Fixed Paraffin-Embedded (FFPE)tissue samples of High-grade serous carcinoma (HGSOC). VISTA, CTLA4, PDL1, PD1, CD8, CD4, and FOXP3 mRNA extracted from 429 patients with ovarian cancer in the Cancer Genome Atlas (TCGA) database was included as a validation cohort. Correlations between these checkpoints, tumor-infiltrating- lymphocytes (TILs), and survival were analyzed. Results and discussion CTLA4 was detectable in 87.3% of samples, VISTA in 64.7%, PD1 in 56.7%, and PDL1 in 48.1%. PDL1 was the only tested protein associated with an advanced stage (p=0.05). VISTA was associated with PDL1, PD1, and CTLA4 expressions (p=0.005, p=0.001, p=0.008, respectively), consistent with mRNA level analysis from the TCGA database. Univariate analyses showed only VISTA expression (p=0.04) correlated with overall survival (OS). Multivariate analyses showed that VISTA expression (p=0.01) and the coexpression of VISTA+/CTLA4+/PD1+ (p=0.05) were associated with better OS independently of the clinicopathological features. Kaplan-Meier analysis showed that the coexpression of the VISTA+/CTLA4+/PDL1+ and VISTA+/CTLA4+/PD1+ checkpoints on tumor cells (TCs)were associated with OS (p=0.02 and p<0.001; respectively). VISTA+/CTLA4+/PD1+ in TCs and CD4+/CD8+TILswere associated with better 2-yer OS. This correlation may refer to the role of VISTA as a receptor in the TCs and not in the immune cells. Thus, targeting combination therapy blocking VISTA, CTLA4, and PD1 could be a novel and attractive strategy for HGSOC treatment, considering the ambivalent role of VISTA in the HGSOC tumor cells.